Effect of nano-textured heater surfaces on evaporation at a single meniscus. (May 2017) - Fischer, Sebastian; Sahu, Rakesh P.; Sinha-Ray, Sumit; Yarin, Alexander L.; Gambaryan-Roisman, Tatiana; Stephan, Peter
Highlights: Evaporation of liquid at a single meniscus on a nano-fiber heater surface studied using infrared thermography. Evaporation at non-moving meniscus in the presence of nanofibers results in enhancement of heat flux transferred from the heater. Receding meniscus on a nano-textured surface leaves behind a broad wetted region, characterized by high heat transfer rate. Propagation of advancing meniscus on a nano-textured surface is a chaotic process leading to formation of regions of high local heat flux. Application of nanofiber coatings in practical two-phase systems is very promising for achieving extremely high cooling rates. Abstract: Nanofiber coatings have shown a unique potential for heat transfer enhancement during drop impact cooling, nucleate boiling and flow boiling. In order to get insights into the mechanisms of heat transfer enhancement invoked by the nanofiber coating, we investigated evaporation of liquid in the vicinity of an apparent contact line of a single meniscus, where the liquid-vapor interface meets the nano-textured substrate. The experiments have been performed for stationary, advancing and receding menisci. It has been found that the local heat flux in the vicinity of a stationary apparent contact line is increased by approximately 60% in the presence of nanofiber coating. The receding meniscus leaves behind an extended region, in which the pores within the nano-textured mat are fully or partially filled with evaporating liquid, which significantly contributes to the heat transfer enhancement. These phenomena can be attributed to very strong capillary forces acting within the porous media and retaining the cooling liquid in contact with the heater surface.